Arsenic : Exposure Sources, Health Risks, and Mechanisms of Toxicity - States, J. Christopher. Ed. (New Jersey : Wiley, 2016)
"This book acts as a compendium of up-to-date knowledge on arsenic as a toxicant, its exposure sources, health risks, and mechanisms"--
Includes index.
Keywords: Arsenic -- Health aspects; Arsenic -- Toxicology; Technology & Engineering / Industrial Health & Safety; Medical / Epidemiology